Gus Dur’s Interreligious Equality in the Context of Plural Indonesian Society - Abdul, Mohd. Rivaldi (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2024)
In the plural Indonesian society, where there are Muslim, Protestant, Catholic, Budha, Hindu, Konghucu, and Penghayat, interreligious harmony is something that cannot be ignored. In this case, the majoritarianism tyranny is an intolerant source that can crack harmony in religious diversity. This article gives a concept of Gus Dur’s teaching about the principle of interreligious equality. Any main questions have been exposed in this article; How is Gus Dur’s partiality toward the non-Muslim minority? How does Islam, which Gus Dur taught, regard other religious people? And why is Gus Dur’s teaching important in the religious context of plural Indonesian society? To answer the questions, to expose Gus Dur’s teaching in this article, the author explored various of Gus Dur’s writings. In this way, the author used the method of library research. According to some findings in this article, diversity for Gus Dur was not only an idea but also a part of his struggle for humanity. Gus Dur always protected humanity without seeing religious status. Gus Dur’s partiality to the non-Muslim minority was strengthened by his belief that all humans, whatever their religions, are brothers and all are equal. Gus Dur taught the principle of interreligious equality.